Evaluation of the performance of heterogeneous electroFenton process with carbon nanotube/Fe@Fe2O3 for the degradation of amoxicillin from aqueous solutions - Nezamaddin Mengelizadeh; Parisa Ebadi; Najmeh Ghazanfari; Somayeh Kohestani (Muhandisī-i Bihdāsht-i Muḥīṭ, 2023)
Background: Effluents discharged from pharmaceutical industries contain toxic and persistent compounds, which have raised concerns among environmentalists in recent decades. Recently, various methods have been used to treat pharmaceutical wastewater, among which the electrooxidation process with its unique features, including high efficiency, low secondary pollutant production, and environmental friendliness, has received more attention. In the present study, the efficiency of heterogeneous electro-Fenton process based on Fe@Fe2O3 nanoparticles loaded on CNTs (CNTs/Fe@Fe2O3) in amoxicillin removal was evaluated. Methods: In this experimental-laboratory study, CNTs/Fe@Fe2O3 nanoparticles were synthesized as particle electrode and Ti/PbO2 as anode electrode, and their characteristics were determined by scanning electron microscope and X-ray scattering pattern. The effect of operating parameters on the amoxicillin removal rate was evaluated by the heterogeneous electro-Fenton process. Comparative tests were conducted between the adsorption and oxidation processes in antibiotic removal, and finally, the stability of the process based on new electrodes was studied in the cycle of successive electrooxidation reactions Results: The results showed that the electrochemical and adsorption processes have a lower removal efficiency than the heterogeneous electro-Fenton process at pH close to neutral. The maximum removal efficiency of amoxicillin was obtained at pH of 6, particle electrode dosage of 250 mg/L, current density of 25 mA/cm2, and electrolysis time of 120 min. The stability of the electrodes was confirmed by the cycle of successive reactions. Conclusion: Based on the findings, the electro-Fenton process based on newly synthesized electrodes can be suggested in the electrooxidation analysis of antibiotics.